Framed women of Ardemore House a novel - Schillace, Brandy (Toronto, Ontario, Canada Hanover Square Press, 2024)
A neurodivergent, hyperlexic book editor, Jo Jones, taking possession of a possibly haunted family estate in North Yorkshire, finds herself at the center of a murder investigation when the groundskeeper is found dead and a family portrait goes missing, and to clear her name, she must unearth the town's secrets--and her own.
113185
Keywords: Women editors -- Fiction; Inheritance and succession -- Fiction; Autistic women -- Fiction; Murder -- Investigation -- Fiction; Secrecy -- Fiction; Secret -- Romans, nouvelles, etc; Yorkshire (England) -- Fiction; Detective and mystery stories; Mystery fiction; Cozy mysteries; Novels; Romans policiers cozy; Romans